THE USE OF TORUS TECHNOLOGIES TO CREATE A METHOD AND DEVICE FOR THE MANUFACTURE OF BORED PILES - Viktor Vasilievich Shishkin; Savva Viktorovich Skorikov; Dmitry Mikhailovich Steshenko (Современная наука и инновации)
Developed a new method of compaction wells and hardening material that fills the well. Described tore a method of manufacturing bored piles and device for its manufacture. Also the fundamentals of rolling torosay shell in the well.